Double Function Random Early Detection (DFRED): A Revised RED-Oriented Algorithm - Hassan, Samuel O.; Ajaegbu, Chigozirim; Solanke, Olakunle O. (Iraqi Journal of Science, 2023)
Dropping packets with a linear function between two configured queue thresholds in Random Early Detection (RED) model is incapable of yielding satisfactory network performance. In this article, a new enhanced and effective active queue management algorithm, termed Double Function RED (DFRED in short) is developed to further curtail network delay. Specifically, DFRED algorithm amends the packet dropping probability approach of RED by dividing it into two sub-segments. The first and second partitions utilizes and implements a quadratic and linear increase respectively in the packet dropping probability computation to distinguish between two traffic loads: low and high. The ns-3 simulation performance evaluations clearly indicate that DFRED algorithm significantly controls the average queue occupancy and yields a reasonable gain in end-to-end-delay under different network conditions.